Analysis of Organic Waste Management of Central Market Pinrang Regency - Arsyad, Arsyad; Arifin, Moh. Aris; Mukrim, Ihsan; Jamaluddin, Jamaluddin; Hamzah, Hamzah; Dirman, Eris Nur; Reno, Reno; Rauf, Abd.; Bauna, Ruslan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Waste is the result of human activities or natural processes. One of the largest sources of waste in urban areas is market waste which can cause public health problems and city aesthetics. The generation of market waste is quite large so that good management is needed so that market waste does not cause problems for city residents. The research method used is descriptive with an observational approach. Sampling was done by stratified random sampling, with a sample size of 230 traders. Data collection was carried out using an observation sheet in the form of a checklist. The results showed that out of 230 traders, 5.2% of traders had containers that met the requirements and 94.8% of traders were in the category of not meeting the requirements. Meanwhile, for storage, 18.7% met the requirements and 81.3% did not meet the requirements. For collection, 31.3% met the requirements and 68.7% did not meet the requirements, while for transportation, 91.7% met the requirements and 8.3% did not meet the requirements. Therefore, traders should replace damaged containers and related agencies should optimize waste management at the Pinrang Central Market